871 The Efficacy and Safety of Bariatric Surgery in Patients with End-Stage Renal Disease Awaiting Listing for Kidney Transplantation: A Systematic Review and Meta-Analysis. (19th August 2022) - Varma, J; Fernando, S; Dengu, F; Menon, V; O'Callaghan, J
Abstract: Aim: Obesity is associated with adverse outcomes in end-stage renal disease (ESRD) and hinders changes for waiting list allocation of kidney transplantation (KT). Bariatric surgery (BS) is an effective solution to obesity. The authors aim to summarise the evidence for the efficacy and safety of BS in ESRD awaiting KT. Method: We performed a systematic review and meta-analysis to determine the efficacy and safety of BS in patients with ESRD awaiting KT. A literature search of MEDLINE, EMBASE and Web of Science was conducted from inception to April 2021. The methodological quality of selected studies was assessed using the Newcastle-Ottowa tool. Our primary outcome was change in BMI, with secondary outcomes including adverse events, graft outcomes and KT listing rate. Results: Nine observational studies met the inclusion criteria with a total of 1903 patients (43.9% male). Mean change in BMI following BS was -11.3 (-15.3 to -7.3, p <0.001) within a median follow up time of 27.6 months (IQR 12 to 36.6 months). Sleeve gastrectomy (44.6%, n=849) and gastric bypass (43.6%, n=829) were the most common procedures. Mean age at BS was 47.3 years with a mean rate to KT listing of 59.9% (SD = 1.13). Conclusion: This review highlights that BS is both safe and efficacious on patients with ESRD and can aid with optimisation for waiting list allocation.